Monetary policy and unemployment in the Republic of serbia - Veselinović, Nevena (Industrija, 2020)
The main objective of the examination is to conclude whether monetary policy can influence the unemployment rate through the key policy rate and to analyze the relationship between inflation and unemployment in the Republic of Serbia, considering that the mentioned occurrences are major destabilizers of the developing economy. The Vector error correction model is used as the central model for inquiring the structure of the time series. From the cointegration equation of the VEC model, it can be concluded that there is no long-run equilibrium dynamic between the key policy rate and the unemployment rate in the Republic of Serbia over the period 2009M1-2019M6. Regarding the relationship between inflation and unemployment, there is a positive statistically significant effect of the inflation rate to the unemployment rate in the long-term. In the short term, results indicate that the key policy rate, as well as the inflation rate, do not cause the unemployment rate in the observed period.